INTEGRATING COMPUTER-ASSISTED LANGUAGE LEARNING (CALL) IN PRIMARY SCHOOL IN SAUDI ARABIA: FEMALE EFL TEACHERS` PERCEPTIONS - Sahla, Shereen Ghazi (Journal of Educational and Psychological Sciences, 2021)
This study explored female EFL teachers’ perceptions about using CALL to teach English in classrooms in Saudi Arabia. The participants were 27 female EFL teachers working in primary schools in Riyadh. The participants were selected using convenience sampling. The researcher employed survey based research design and the data was collected via a questionnaire based on the study of (Alshehri, 2018). The study findings revealed the teachers have positive perception using CALL in the classroom, and that they are aware CALL has a significant influence on both their teaching and students’ learning. Moreover, the study found no statistically significant differences at (α = 0.05) between Saudi female EFL teachers’ perceptions of CALL use in primary schools arising from teaching experience. The study recommended improving the infrastructure needed to provide of CALL throughout all schools, and intensifying the training of teachers in ICT use in the classroom.